2015
DOI: 10.1007/s00464-015-4444-y
|View full text |Cite
|
Sign up to set email alerts
|

The First Decade of Laparoscopic Pancreaticoduodenectomy in the United States: Costs and Outcomes Using the Nationwide Inpatient Sample

Abstract: reVista de reVistas the First decade of laparoscopic pancreatico-duodenectomy in the united states: costs and outcomes using the nationwide inpatient sample. Tran TB,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
81
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 26 publications
1
81
1
Order By: Relevance
“…Postoperative mortality was recorded to range from 3.2% to 8.8% in LPD vs. 3.4% to 5.7% in OPD, difference which was not statistical significant (7,39,40,43). The reported incidences of clinical relevant POPF (grades B and C) described in several studies were fairly similar, ranging from 6.3% to 11.0% (45,49) in LPD and 5% to 9% (40,43) in open surgery.…”
Section: Pancreatoduodenectomy (Pd)mentioning
confidence: 85%
See 1 more Smart Citation
“…Postoperative mortality was recorded to range from 3.2% to 8.8% in LPD vs. 3.4% to 5.7% in OPD, difference which was not statistical significant (7,39,40,43). The reported incidences of clinical relevant POPF (grades B and C) described in several studies were fairly similar, ranging from 6.3% to 11.0% (45,49) in LPD and 5% to 9% (40,43) in open surgery.…”
Section: Pancreatoduodenectomy (Pd)mentioning
confidence: 85%
“…Moreover, several studies (39,47,48) have indicated that the learning curve is steep, DOS is increased and total costs are higher in centers performing fewer PDs. According to Adam and colleagues in their analysis of 7,061 PD for cancer in the US from 2010-2011, 92% of LPD (14% of all PDs) were undertaken in hospitals performing 10 LPD or less over a 2-year period.…”
Section: Pancreatoduodenectomy (Pd)mentioning
confidence: 99%
“…The clinical equivalence in terms of oncological integrity, fast track protocol compliance, PROs, survival benefits and MIS reproducibility have been established in the index GIM [17,18]. Assimilation of Pancreaticoduodenectomy (PD) into MIS repertoire has been slow as evident from reports of only 4% PDs being done by MIS, in decade long US data base volume of more than 15,000 PDs [19]. Apart from the 'learning proficiency curve' (LCP) issues, this slow adoption of minimally invasive PDs (MIPD) is attributable to the retroperitoneal location of pancreas, its proximity to major vessels, prevalence of aberrant major vessels, and propensity for major postoperative complication [19].…”
mentioning
confidence: 99%
“…Assimilation of Pancreaticoduodenectomy (PD) into MIS repertoire has been slow as evident from reports of only 4% PDs being done by MIS, in decade long US data base volume of more than 15,000 PDs [19]. Apart from the 'learning proficiency curve' (LCP) issues, this slow adoption of minimally invasive PDs (MIPD) is attributable to the retroperitoneal location of pancreas, its proximity to major vessels, prevalence of aberrant major vessels, and propensity for major postoperative complication [19]. There is hope, as high impact studies about MIS in different surgical anatomies have plateaued for cholecystectomy while being increasingly published for GIMs as shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation